WORKSHOP STRATEGI BRANDING WORKSHOP STRATEGI BRANDING DAN DIGITAL MARKETING PRODUK INOVASI OLAHAN SUSU SAPI PERAH DESA GERBO: WORKSHOP STRATEGI BRANDING DAN DIGITAL MARKETING PRODUK INOVASI OLAHAN SUSU SAPI PERAH DESA GERBO - Tirtoni, Feri; Supriyadi; Arya Wahyu Ramadhan (Kanigara, 2024)
The existence of MSMEs is an effort to boost the economy in Gerbo village to make it more independent and self-sufficient. This seems to have happened in the community of Gerbo village where there is an MSME producing dairy milk that is actively operating in this village, therefore we, the KKN team, will carry out community service through workshop efforts which aim to transfer knowledge in the form of branding and marketing for MSMEs. carry out an innovation in dairy milk and carry out branding in terms of packaging and quality which we can add economic value to and this effort will later be continued with marketing efforts to open a marketing network which can be done online or in other ways. Our activities will be carried out in two stages, namely socialization to provide initial knowledge to the community and continued through a workshop activity to provide a tutorial and practice on how to innovate dairy milk products in the Buffalo village and in the workshop we will later be taught marketing techniques. for the future continuity of these MSMEs. Cow's milk is a type of drink that has good nutritional content for body health and brain intelligence. ABDIMAS aims to make herbal cow's milk as a health herbal drink. ABDIMAS utilizes the abundant pure cow's milk in Gerbo village. Herbal cow's milk is milk that comes from a mixture of herbal spices. ABDIMAS aims to increase the selling value of cow's milk and boost the economy of the community in Gerbo village. The method used in ABDIMAS is observation and interviews through several stages, starting with discussion and observation of the targets of the service program. This ABDIMAS has produced results in solving the problems faced by the Gerbo village community. So it is hoped that making herbal cow's milk can increase income for the people of Gerbo village and open up employment opportunities for the community.